Relationship between Damage Rate of High-Voltage Electrical Equipment and Instrumental Seismic Intensity - Rushan Liu; Mingpan Xiong; Deyuan Tian (Advances in Civil Engineering)
Based on the actual damage data of high-voltage electrical equipment in electric substations in the Wenchuan earthquake, this paper uses the cumulative Gaussian distribution function to describe the relationship between the damage rate of high-voltage electrical equipment and the instrumental seismic intensity. The instrumental seismic intensity at strong motion observation stations in the Wenchuan earthquake is calculated, and the Kriging interpolation method is used to estimate the instrumental seismic intensity at 110 kV and above voltage level substations in Mianyang, Deyang, Guangyuan, and Chengdu of Sichuan Province. A cumulative Gaussian distribution function is then used to fit the damage rate-instrumental seismic intensity relationship curve for six types of high-voltage electrical equipment such as the transformer, circuit breaker, voltage mutual inductor, current mutual inductor, isolating switch, and lightning arrester. The results show that transformers have the highest vulnerability during earthquakes, and they suffered a certain level of damage even under low instrumental intensity. The second most vulnerable equipment is the circuit breaker, followed by the lightning arrester, transformer, and isolating switch, which share a similar vulnerability curve.